Implementation of Good Governance Principles in Land Certification Services at National Land Agency of Konawe Regency - Jenriawan; Edi Tadung; Indrawan Tobarasi; Siti Jahria Sitompul (Journal of Social and Policy Issues, 2021)
This research aims to determine the application of good governance principles in land certification services at the National Land Agency (BPN) of Konawe Regency, namely on the dimensions of professionalism, transparency, excellent service, efficiency and effectiveness. This research used a qualitative method with a descriptive approach to know about professionalism, transparency, excellent service, efficiency and effectiveness in the land certification process. Research data sourced from interviewed with research informants, observations and secondary data from various literatures. Results of this research indicated that the principles of good governance in the dimensions of professionalism, transparency, excellent service, efficiency and effectiveness in land certification services at BPN Konawe have not been applied optimally. On dimension of excellent service, there was no clear information or announcement regarding the standard cost and time in the land certification process, thus making the community did not know for sure about the amount of costs and the required time period. On efficiency dimension has also not been implemented optimally, this can be seen by the issuance of several land certificates which take up to 98 working days.